Soil carbon fluxes and balances of crop rotations under long-term no-till - Rigon, João Paulo Gonsiorkiewicz [UNESP]; Calonego, Juliano Carlos [UNESP] (Springer Nature, 2020)
Background: A field study with the same crop rotations was conducted to test the hypothesis that the soil Carbon fluxes and balances could vary according to the crop species and also mitigate carbon dioxide (CO2) emission. This study aimed to assess the CO2 emission from crop rotations according to C and N inputs from crop residue, the influences on soil organic carbon (SOC) and total soil nitrogen (TN) stocks, identifying the soybean production systems with positive C balance. Triticale (x Triticosecale) or sunflower (Helianthus annuus) are grown in the fall/winter; sunn hemp (Crotalaria juncea), forage sorghum (Sorghum bicolor), pearl millet (Pennisetum glaucum), or fallow are the spring treatments, and soybean as a main crop in summer. Results: We found that high C inputs from crop residues modify the C dynamics in crop rotations by reducing the C output (CO2) and increasing C sequestration in the soil. In general, the higher SOC, C stocks, and TN in soil surface were due to higher C and N inputs from sunn hemp or forage sorghum crop residues in spring. These crops also produced lower accumulated CO2 emissions and, when rotating with triticale in the fall-winter season resulted in a positive C balance, making these soybean crop rotations more efficient. Conclusion: Our study suggests the ideal crop species choice in a rotation can mitigate the CO2 emissions by increasing C and N input from crop residues and consequently SOC and C stocks. In particular, crop rotation comprises an important tool to achieve a positive C balance, mitigate CO2 emissions and provide an additional ecosystem service to soybean cultivation option.
Keywords: C and N inputs; Cover crop; Crop straw; Cropping system